Diagnostic yield of stool culture and predictive factors for positive culture in patients with diarrheal illness. Issue 30 (July 2017) - Lee, Jae Young; Cho, Sun Young; Hwang, Hannah Sun Hae; Ryu, Ja Young; Lee, Jongjin; Song, In Do; Kim, Beom Jin; Kim, Jeong Wook; Chang, Sae Kyung; Choi, Chang Hwan
Abstract : Abstract: We aimed to investigate the diagnostic yield of stool cultures and identify predictive factors for positive cultures in patients with diarrheal illness. A total of 13, 327 patients who underwent stool cultures due to diarrheal illness were reviewed. Stool cultures were performed for enteric pathogens, including Salmonella, Shigella, Vibrio, Klebsiella oxytoca, and Yersinia . The culture-positive group was compared with the culture-negative group who were randomly selected from culture negative patients. A total of 196 patients (1.47%) were diagnosed with positive stool culture. In 196 culture positive patients, Salmonella spp. (75.0%) was detected most commonly, followed by Vibrio (19.4%). Univariate analyses showed fever (>37.8°C), vomiting, duration and frequency of diarrhea, and high C-reactive protein (CRP) were significantly associated with positive stool culture. Multivariate analysis showed fever (odds ratio [OR], 2.33; 95% confidence interval [CI], 1.25–4.35; P  = .008), ≥5/day of diarrhea (OR, 3.52; 95% CI, 1.93–6.44; P  < .001) and >50 mg/L of CRP (OR, 2.27; 95% CI, 1.18–4.36; P  = .014) were independent predictors for positive stool culture. OR in patients with all 3 factors was 6.55 (95% CI, 2.56–16.75; P  < .001). Vomiting (OR, 0.32; 95% CI, 0.17–0.57; P  < .001) was a negative predictive factor. Diagnostic yield of stool culture in patients with diarrheal illness is very low. Fever, frequency of diarrhea, and high CRP are predictors for positive stool cultures. These findings may lead to more discerning and cost-effective utilization of stool culture by clinicians.